[(1,2,5,6-η)-Cycloocta-1,5-diene](1-ethyl-4-isopropyl-1,2,4-triazol-5-ylidene)(triphenylphosphane)iridium(I) tetrafluoridoborate dichloromethane sesquisolvate - Aaron Maynard; Michael Gau; Daniel R. Albert; Edward Rajaseelan (IUCrData, 2023)
The synthesis and crystal structure of a new triazole-based N-heterocyclic carbene iridium(I) cationic complex with a tetrafluoridoborate counter-anion and solvating dichloromethane, [Ir(C8H12)(C7H13N3)(C18H15P)]BF4·1.5CH2Cl2, is reported. The IrI center of the cationic complex has a distorted square-planar conformation, formed by a bidentate cycloocta-1,5-diene (COD) ligand, an N-heterocyclic carbene, and a triphenylphosphane ligand. There are weak hydrogen-bonding interactions between C—H groupings of the iridium complex and F atoms of the [BF4]− counter-ions. The atoms of the COD ligand are disordered over two sets of sites in a 0.65:0.35 ratio and two of the F atoms of the anion are disordered over adjacent sites in a 0.6:0.4 ratio. One of the dichloromethane solvent molecules is disordered about an inversion center with 0.5 occupancy.